Conference Wolves in Sheep’s Clothing - Sorooshian, Shahryar (Springer Netherlands, 2017)
In some cases, organizing a conference resembles a high-profit business. Some of these conferences are wolves in sheep’s clothing. This article draws readers’ attention to current examples of such unethical business conferences.